The Permeability Transition in Plant Mitochondria: The Missing Link - Zancani, Marco; Casolo, Valentino; Petrussa, Elisa; Peresson, Carlo; Patui, Sonia; Bertolini, Alberto; De Col, Valentina; Braidot, Enrico; Boscutti, Francesco; Vianello, Angelo (Frontiers in Plant Science, 2015)
The synthesis of ATP in mitochondria is dependent on a low permeability of the inner membrane. Nevertheless, mitochondria can undergo an increased permeability to solutes, named permeability transition (PT) that is mediated by a pore (PTP). PTP opening requires matrix Ca2+ and leads to mitochondrial swelling and release of intramembrane space proteins (e.g. cytochrome c). This feature has been initially observed in mammalian mitochondria and tentatively attributed to some components present either in the outer or inner membrane. Recent works on mammalian mitochondria point to mitochondrial ATP synthase dimers as physical basis for PT, a finding that has been substantiated in yeast and Drosophila mitochondria. In plant mitochondria, swelling and release of proteins have been linked to programmed cell death, but in isolated mitochondria PT has been observed in only a few cases and in plant cell cultures only indirect evidence is available. The possibility that mitochondrial ATP synthase dimers could function as PTP also in plants is discussed here on the basis of the current evidence. Finally, a hypothetical explanation for the origin of PTP is provided in the framework of molecular exaptation.